Feminisme Islami: Suatu Kritikan Terhadap Faham Keadilan Musawah: Islamic Feminism: A Critique of Musawah’s Conception of Justice - Ahmad, Md. Asham (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
This article refutes the concept of justice promulgated by Musawah, a Malaysia-based feminist organization as anti-thetical to the worldview of Islam, and describes it as an effort to secularize the Muslim’s mind. Based on an analysis of the concept, the article argues that feminist ideology camouflaged as ‘Islamic feminism’ is an attempt to confuse the Muslims in aiming to effect change to Islamic law and ultimately Islam itself.